Determinants of Behavioral Intention in Adopting Network Monitoring System - Mugerwa, Shafiq; Moya, Musa B.; Mayoka Kituyi, Geoffrey (International Journal of Computer Applications Technology and Research, 2018)
Makerere University Business School(MUBS) staff and student population stands to over 15,000 (MUBS HR report 2014) but on average, MUBS digitized online network can support about 700 users pick time and approximately 300 off pick hours which is not sufficient (Management Information Systems Unit Network statistics, 2015). Could the low support be attributed to the determinants of behavioral intention? This study therefore examined the relationships between performance expectancy, effort expectancy, social influence, facilitating conditions and behavioral intentions in the adoption of an integrated network monitoring system (NMS) at Makerere University Business School (MUBS). The study followed a cross sectional quantitative research design that focused on describing and drawing inferences from the findings on the relationship between the variables. The study population comprised of 189 administrative staff using the survey instrument based on the UTAUT constructs tailored for the study. Data was analyzed using descriptive statistics, correlations and regressions analysis using Statistical package for social sciences (SPSS). The results indicate that there were significant positive relationships between Performance Expectancy, Effort expectancy Social influence and Facilitating Conditions on Behavioral intention. Emphasis should be placed on performance expectancy, effort expectancy, social influence and facilitating conditions as determinants of behavioral intention for better network monitoring system.
Keywords: Network monitoring system; UTAUT; Behavioral intention; Performance expectancy; Effort expectancy; Social influence and facilitating conditions